Tinjauan Tata Ruang Unit Rekam Medis dalam Menjaga Keamanan dan Kerahasiaan Rekam Medis di RSUD Kembangan - Tri Putra, Iqbal; Fannya, Puteri; Widjaya, Lily; Muniroh, Muniroh (Cerdika: Jurnal Ilmiah Indonesia, 2022)
In the Medical Record Unit of the Kembangan Regional General Hospital, the work space of the medical record unit is directly related to the active medical record storage room, the door of the medical record unit at the Kembangan Regional General Hospital does not yet have a secret key or additional security such as a fingerprint. The purpose of this study was to determine the layout of the medical record unit in maintaining the security and confidentiality of medical records at the Kembangan Regional General Hospital. This study used quantitative descriptive methods with observation and interview data collection techniques, as well as direct measurements in the workspace and storage of the medical record unit of the Kembangan Regional General Hospital using a measuring instrument in the form of a building meter, then to determine the need for storage space obtained from the calculation of shelf requirements. medical record storage using the formula according to the International Federation of Health Information Management Associations. The results of the research are in the medical record unit of the Kembangan Regional General Hospital already have standard operating procedures related to the security and confidentiality of medical records but in practice it has not been implemented optimally. Inadequate facilities and infrastructure can be seen from the current work area of 10.27 m3, it should takes 15 m3, the storage space is still minimally lit and does not meet the standards. Suggestion: it is better if standard operating procedures have not been implemented to be implemented immediately.